Modularity and specialization in bat–fly interaction networks are remarkably consistent across patches within urbanized landscapes and spatial scales. Issue 4 (13th December 2020) - Urbieta, Gustavo Lima; Graciolli, Gustavo; Vizentin-Bugoni, Jeferson
Abstract: Patterns of specialization and the structure of interactions between bats and ectoparasitic flies have been studied mostly on non-urban environments and at local scales. Thus, how anthropogenic disturbances influence species interactions and network structure in this system remain poorly understood. Here, we investigated patterns of interaction between Phyllostomidae bats and ectoparasitic Streblidae flies, and variations in network specialization and structure across Cerrado patches within urbanized landscapes in Brazil and between local and regional scales. We found high similarity in the richness and composition of bat and fly species across communities, associated with low turnover of interactions between networks. The high specialization of bat–streblid interactions resulted in little connected and modular networks, with the emergence of modules containing subsets of species that interact exclusively or primarily with each other. Such similarities in species and interaction composition and network structure across communities and scales suggest that bat–fly interactions within Cerrado patches are little affected by the degree of human modification in the surrounding matrix. This remarkable consistency is likely promoted by specific behaviors, the tolerance of Phyllostomidae bats to surrounding urbanized landscapes as well as by the specificity of the streblid–bat interactions shaped over evolutionary time.